Phenotypes in children with GNAO1 encephalopathy in China - Li, Yanmei; Chen, Hong; Li, Lin; Cao, Xueyan; Ding, Xin; Chen, Li; Cao, Dezhi (Frontiers in Pediatrics, 2023)
Background: The GNAO1 gene encodes the α-subunit (Gαo) of the heterotrimeric guanine nucleotide-binding protein (G protein). The aim of this study was to explore the clinical characteristics of patients with GNAO1 gene variations. Methods: Ten patients with variations in GNAO1 were enrolled from the Shenzhen Children's Hospital. Clinical data from several cases previously reported from China were also included and analyzed. Results: Twenty-seven patients with variations in GNAO1 were analyzed (10 patients from Shenzhen Children’s Hospital, 17 patients from previously published studies) including 12 boys and 15 girls. The median age of onset was 3 months with moderate to severe global developmental delay. Nineteen different GNAO1 heterozygous variants were identified. Epilepsy was observed in 18 patients (67%,18/27), movement disorder (MD) was observed in 22 patients (81%,22/27), and both were seen in 13 patients (48%,13/27). Seizures typically presented as focal seizures in all patients with epilepsy. MD typically presented as dystonia and chorea. Loss-of-function (LOF) or partial loss-of-function (PLOF) mutations were more frequent in patients with developmental and epileptic encephalopathy (p=0.029). Interictal electroencephalograms showed multifocal or diffuse epileptiform discharges. The most common magnetic resonance imaging finding was widened extracerebral space. In contrast to MD, in which improvements were not common, seizures were easily controlled by anti-seizure medications. Severe dystonia in three patients was effectively treated by deep brain stimulation. Seven (26%, 7/27) patients died of respiratory complications, status dystonicus, choreoathetosis, or sudden unexpected death in epilepsy. Conclusion: We analyzed clinical data of 27 cases of GNAO1-related encephalopathy in China. MD seemed to be the central feature and was most difficult to control. LOF or PLOF variants were significantly associated with developmental and epileptic encephalopathy. The active intervention of severe dystonia may prevent death due to status dystonicus. However, future studies with larger samples are needed to confirm these results.